La ilegalidad de la acumulación de penas en el delito de posesión de sustancias estupefacientes, artículo 220 numeral 1 del código integral penal - Guapulema García, Landy Bayardo (2017)
This thesis makes consideration of a socio-legal investigative work, which is aimed at proposing a serious study to allow the legislator and judicial officials to find a fair and just solution to the problem of illegal accumulation of penalties for the traffic offense of scheduled substances connected to control. As liberty is a valued legally, it demands that the justice of a State is guarantor of the rights of its citizens without discriminate the legal status in which they are. With it arises the urgent need to make prevail the principles governing the legal harmony of a society. Furthermore, when these have been threatened by inappropriate development of laws that in some cases are not in line with social reality. Penal guarantees judges have had a difficult task in relation to administer justice. The application of Article 220, paragraph 1 of the Integral Penal Code in relation to punish ilegal traffic of scheduled substances connected to control has produced an avalanche of challenges, appeals by lawyers and defenders who have demonstrated how the accumulation of penalties breaks the principle of legality and has made a debate for the possibility to reform the mentioned article as a legal solution to this controversial issue. The current situation calls for serious analysis and a fair decision to find a solution by the National Assembly, in order that the judges can judge the offenders in drug trafficking, without having to give them an accumulation of unjust punishment, when it is shown that the Article 220.1 of the Integral Penal Code causes accumulation of penalties, based on an interpretation of scale provided by CONSEP which was modified and is the legal remedy to accumulate penalties. This investigative work has an urgent need to propose an integral reform of the Article 220.1 of COIP in the Second Section, crimes for the production or trafficking of scheduled substances connected to control.